Efficacy of Exercise Interventions Applied to Populations Diagnosed With Eating Disorder(s) on Health Outcomes - Weatherby, Kaitlyn; Prince, Marissa; Hoffman, Patrick; Anderson, Lauren; Houser, Jared; Karnish, Kristen (Archives of physical medicine and rehabilitation, 2022)
Investigate the impact of resistance training, yoga, and aerobic exercise on perceived quality of life and physiological function for individuals with eating disorders. EBSCO-PsycINFO, EBSCO-Health Source, PubMed, and CINAHL were searched in September 2021 and January 2022. Indexing terms used for article retrieval included the combination of: physical therapy, physiotherapy, rehabilitation, eating disorder, anorexia nervosa, bulimia nervosa, binge eating, exercise, exercise interventions, resistance training, yoga, and aerobic exercise. Eligible articles included English translation, peer-reviewed, publication date after 2009, subjects < 50 years old, interventions within physical therapy scope of practice including resistance training, yoga, or aerobic training, and PEDro score ≥ 3. Seventy articles were retrieved for evaluation. Studies were selected following consensus by multiple researchers. Eleven articles met inclusion criteria. Articles were analyzed for quality and validity using the PEDro scale and a hierarchy of evidence scale. Data extracted from each article included subject demographics, interventions provided, assessment tools, outcomes, limitations, and conclusions. Researchers found that for all participants diagnosed with eating disorders, high intensity resistance training was more effective in improving and maintaining QOL and functional strength measures as compared to low/moderate intensity exercise. Experimental groups who performed yoga or received cognitive behavioral therapy with resistance interval training demonstrated increased psychological well-being and emotional regulation. Exercise had a positive effect on BMI and frequency of binge-eating behaviors in individuals with binge eating disorder. Physiological measures were also improved in subjects who engaged in physical activity alongside counseling with a mental health physical therapist. Inclusion of exercise for individuals receiving eating disorder treatment can positively affect perceived quality of life, body composition, and physiological function. Future research is recommended to explore the role of physical therapy in eating disorder treatment including investigation of long-term intervention effects and treatment along the continuum of recovery. No conflicts of interest present.